واقع استخدام الحاسب الآلي في تدريس العلوم في المدارس الثانوية للبنات بالمدينة المنورة : التحديات والحلول - طاهر، أمل محمد ثابت (Ma'had al-Tarbiyyah, al-Jami'ah al-Islamiyah al-'Alamiyah, 2014)
The purpose of the current study is to diagnose the use of computers in teaching science in the female high schools in AL-Medina El-Menawara, Saudi Arabia. The study identifies the challenges that impede science teachers, and propose solutions to these challenges using the descriptive method. The instrument used for data collection was a questionnaire which was conducted to (257) teachers of the science subject who constituted the sample of the study during the second semester of the school year 2012/2013. Regarding the data analysis, SPSS software, version 20, was used for the descriptive statistics including frequencies, percentages, averages, standard deviations in addition to the reliability test of the instrument where Cronbach's Alpha reached (.73). All the questionnaire items were ranked according to the five-point Likert scale of agreement. The results of the study revealed that the science teachers of female high schools in AL-Medina are facing many challenges regarding teaching using computers. The results also showed that the extent to which the teachers use computer was moderate. Finally, the study concluded that teachers are, by individual efforts, ready for teaching science using computers. According to the results, the challenges lie in the curriculum and some other issues related to the Ministry of Education, such as the lack of training to help teachers use computers in schools, classroom readiness for using computers, difficulty of obtaining computerized curriculum and the high costs of computers maintenance in addition to the insufficient funds for purchasing computers.